Venue of catheter insertion does not significantly impact the event of central line-associated bloodstream infection in patients with haematological diseases. Issue 2 (June 2020) - Kitamura, Hiroaki; Kubota, Yasushi; Komukai, Sho; Yoshida, Hisako; Kaneko, Yukari; Mihara, Yukiko; Nagasawa, Zenzo; Kawaguchi, Atsushi; Aoki, Yosuke; Kimura, Shinya
Summary: Background: Central line-associated bloodstream infection (CLABSI) is a serious complication of central venous catheter (CVC) placement in patients with haematological diseases associated with neutropenia and immunosuppression. However, whether the venues where CVC are inserted influence CLABSI development remains unclear. Methods: We investigated whether CVC insertion at venues with different standards of cleanliness altered the occurrence of CLABSI. We evaluated data from 279 patients (545 CVC insertions) with haematological diseases including age, sex, underlying disease, reason for insertion, insertion site, number of lumens, venue, dates of insertion and removal, complete blood counts, percentage of neutrophils and serum albumin concentrations at the time of CVC insertion. Findings: Overall, 55 CLABSI events occurred during a period of 23, 434 catheter days (2.35 per 1, 000 catheter days). In total, 153 and 190 patients underwent 226 and 305 CVC insertions, respectively in a ward and in an operating room, respectively. Univariate analysis identified the operating room ( P  = 0.017), allogeneic haematopoietic stem cell transplantation ( P < 0.001), triple lumen catheter ( P  = 0.002), haemoglobin ( P  = 0.019), white blood cell count ( P  = 0.012) and percentage of neutrophils ( P  = 0.012) as significant factors for the development of CLABSI. However, multivariate analysis adjusted for age, reason for insertion, insertion site, number of lumens, haemoglobin, percentage of neutrophils and platelet counts found no significant differences between the venue where CVC were inserted and CLABSI development ( P  = 0.158). Conclusion: The venue of CVC insertion is unlikely to influence CLABSI development in patients with haematological diseases.